2020
DOI: 10.21203/rs.3.rs-26423/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Timing of immune checkpoint inhibitors for metastatic patients over 75 years of age: the earlier the better

Abstract: Background The impact of ageing on Immune Checkpoint Inhibitors (ICIs) effectiveness remains controversial. However, data from clinical studies do not show any difference between patients over 65 years and those under 65 years. We focused our study on patients over 75 and looked at the potential impact of timing in the use of ICIs. Methods We performed a meta-analysis of published randomized control trials (RCTs) concerning ICIs versus standard therapy in patients with advanced solid tumors. Overall Survival (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Intriguingly, subgroup analysis on age demonstrated that PD-1/PD-L1 inhibitors could considerably prolong the OS of gastroesophageal cancer patients regardless of the patient's age. In general, aging significantly impacts normal cells in the tumor microenvironment, causing frailty in older patients to limit their capacity to receive further treatment (Landre et al, 2020). However, after the variables including line of therapy, therapeutic schedules, and tumor types were merged with age for pooled analysis, significant potential curative effects with PD-1/PD-L1 inhibitors were observed in the <65 or ≥65 years subgroups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intriguingly, subgroup analysis on age demonstrated that PD-1/PD-L1 inhibitors could considerably prolong the OS of gastroesophageal cancer patients regardless of the patient's age. In general, aging significantly impacts normal cells in the tumor microenvironment, causing frailty in older patients to limit their capacity to receive further treatment (Landre et al, 2020). However, after the variables including line of therapy, therapeutic schedules, and tumor types were merged with age for pooled analysis, significant potential curative effects with PD-1/PD-L1 inhibitors were observed in the <65 or ≥65 years subgroups.…”
Section: Discussionmentioning
confidence: 99%
“…However, after the variables including line of therapy, therapeutic schedules, and tumor types were merged with age for pooled analysis, significant potential curative effects with PD-1/PD-L1 inhibitors were observed in the <65 or ≥65 years subgroups. A previous meta-analysis targeted at age also revealed that in the first line treatment, PD-1/PD-L1 inhibitors were effective not only for patients aged <75 years, but also for patients aged >75 years (Landre et al, 2020). Thus, the upper age limit of PD-1/PD-L1 inhibitors might need to be re-assessed in the future.…”
Section: Discussionmentioning
confidence: 99%